Impact of precipitous labor on the onset of transient tachypnea in vaginal deliveries at term. Issue 3 (20th December 2021) - Jegard, Claire; Korb, Diane; Rideau, Aline; Sibony, Olivier
Abstract: Objective: The objective of the present research was to study the association between precipitous labor (less than 3 h) and the onset of transient tachypnea in singleton fetuses in cephalic presentation with term vaginal deliveries. Methods: This cohort study included women delivered from 2013 through 2017 in our French tertiary university hospital maternity unit. Inclusion criteria were vaginal delivery of liveborn singleton fetus in cephalic presentation and at term. We compared women with precipitous labor and those with longer labor. The principal endpoint was the rate of transient tachypnea of the newborn (TTN). We investigated risk factors for TTN besides duration of labor. Results: Comparison of 2644 women with precipitous labor and 7571 with longer labor showed a lower TTN rate in the precipitous labor group (1.6 vs 2.7%; P  = 0.003). The association was no longer significant after adjustment for the risk factors identified in the univariate analysis (adjusted OR 0.99, 95% CI 0.64–1.54). Risk factors identified for TTN were non‐clear amniotic fluid, shoulder dystocia, umbilical cord encirclement, birth weight less than 2500 g, use of cervical ripening and operative vaginal delivery. Conclusion: Precipitous labor, lasting less than 3 h, is not associated with a higher risk of transient tachypnea in term newborns after vaginal delivery. Abstract : Precipitous labor, lasting less than 3 h, is not associated with a higher risk of transient tachypnea in term newborns after vaginal delivery.